Synthesis and Characterization of Pyrochlore Oxides Bi2MM’O7 (M : Yb, Nd, Sm; M’ : Sb, Nb, Ta) - Suwardiyanto Suwardiyanto; Djulia Onggo; Ismunandar Ismunandar (Indonesian Journal of Physics, 2005)
Oxide compounds Bi2MM’O7 (M : Yb, Nd, Sm; M’ : Sb, Nb, Ta) have been synthesized by using solid state reaction. As a tool for predicting their stability, a stability field diagram for pyrochlore has been made. All the prepared oxides have a yellow color, except for M = Nd which is grey. Crystal structure types have been determined using powder X-ray diffraction. Single phase pyrochlore was obtained for Bi2SmSbO7, while for Bi2NdSbO7 a distorted pyrochlore was obtained. Ideal pyrochlores with small amount of Bi1.5Yb0.5O3 were obtained in Bi2YbSbO7. For Bi2MNbO7, (M : Yb, Nd, Sm) series the obtained phases were a mixture of ideal pyrochlore and small impurities of β-Nb2O5. For Bi2MTaO7 (M : Yb, Nd, Sm) series in addition to ideal pyrochlore as major phase, a small amount of MTaO4 (M : Yb, Nd, Sm) rutile phase were obtained. These observations were explained using the constructed structure map and the lattice energy arguments.